Biotechnology: A key element in the CGIAR's livestock research programme - Teale, A.J. (1997)
The unique potential of biotechnology to provide new solutions to old problems constraining the contribution of livestock to farming systems in the developing world is emphasized in this paper. An overview of biotechnological aspects of livestock research within the CGIAR, including a description of the research approaches being adopted at the International Livestock Research Institute is provided. The products of the research are then identified, and their potential applications in disease diagnosis and vaccination, as well as in the fields of animal breeding and genetic improvement, are described.